Disiplin kerja dalam meningkatkan kinerja perawat melalui motivasi sebagai variabel intervening - Marro Arifah; Helmi Buyung Aulia Safrizal; A.S Fathor (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2020)
This study aims to examine the effect of work discipline in improving nurse performance and to examine the mediating role of motivation. The study used a quantitative approach at the Syarifah Ambami Rato Ebu Bangkalan Regional Hospital. Data collection using a questionnaire to 72 nurses as respondents. The research variables consisted of work discipline, nurse performance and motivation as mediating variables. Data analysis using Path Analysis. The results showed that work discipline has a positive and significant effect on nurses' performance; Work discipline has a positive and significant effect on nurses' motivation, then nurses' motivation has a positive and significant effect on nurses' performance. So motivation plays a role in mediating the effect of work discipline on nurse performance.